Carbon Nanotubes-Based Proton conductors for High Temperature Proton Exchange Membrane (PEM) Fuel Cells - Fatima, Iffat (2025)
A Master of Science thesis in Chemical Engineering by Iffat Fatima entitled, “Carbon Nanotubes-Based Proton conductors for High Temperature Proton Exchange Membrane (PEM) Fuel Cells”, submitted in November 2025. Thesis advisor is Dr. Amani Al-Othman. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).